THE ROLE OF THE CREDIT SYSTEM IN FINANCING SMALL BUSINESS AND ENTREPRENEURSHIP - Rustamov Umidjon Khayitboyevich; Ibrohimov Boburmirzo Bakhtiyor ogli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article provides an in-depth analysis of the role of the credit system in the development of small business and entrepreneurship and its impact on economic growth. In a market economy, the need for financial resources of business entities encourages them to use credit sources rationally. In this regard, the banking and credit system is recognized as an important financial mechanism for supporting small businesses. The article analyzes the measures being implemented in the Republic of Uzbekistan on the basis of state policy, presidential decrees and government resolutions aimed at financially stimulating small businesses. It also studies the effectiveness of preferential loans of commercial banks, microfinance programs and projects implemented in cooperation with international financial institutions. The results of the study serve to determine the role of the credit system in ensuring financial stability for small business entities, to develop proposals for improving credit policy and increasing the competitiveness of the economy.